Commodity Prices, the DJIA, and Inflation as Determinants of the Indonesian Composite Stock Price Index during COVID-19: An Empirical Analysis (2020–2022) - Erlynda Yuniarti Kasim; Marsal Muhamad Dejan (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The COVID-19 crisis created an exceptional combination of falling economic activity, volatile energy prices, cross-border financial spillovers, and changing domestic inflation. This study investigates whether West Texas Intermediate (WTI) crude oil prices, the Dow Jones Industrial Average (DJIA), and Indonesia’s inflation rate were associated with movements in the Indonesian Composite Stock Price Index (IHSG) between March 2020 and December 2022. The analysis uses 34 monthly observations and applies a quantitative explanatory design, descriptive statistics, multiple linear regression, classical diagnostic tests, partial t-tests, a simultaneous F-test, and the coefficient of determination. The findings indicate that WTI prices, the DJIA, and inflation each have a positive and statistically significant relationship with the IHSG, with t-values of 4.144, 5.249, and 4.887, respectively. The predictors are also jointly significant (F = 134.935; p < 0.001), and the model explains 93.1% of the observed variation in the IHSG. The DJIA provides the strongest statistical signal, underscoring the role of global market sentiment. The study contributes by combining a global commodity indicator, an international equity-market benchmark, and a domestic price indicator in one Indonesian pandemic-period model. Because the sample is limited and the residuals exhibit positive serial correlation, the results should be interpreted as exploratory associations and validated in future research using dynamic time-series techniques.